Composite particle, positive pole piece, battery and electric equipment
By using composite particles in the cell electrode sheet, the metal oxide layer with variable ion conductivity controls the discharge and reabsorption of lithium ions, the capacity climbing problem of the cell electrode sheet in the early stage of circulation is solved, and the circulation performance and energy density of the battery are improved.
Patent Information
- Application Number
- CN202411881617.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-21
AI Technical Summary
The existing battery cell chips are prone to capacity climbing in the early stages of circulation, which affects the cycling performance of the battery.
Compound particles are used, which consist of lithium iron phosphate as the core, a carbon layer as the first cladding layer, and a metal oxide layer as the second cladding layer. The ionic conductivity of the second cladding layer is variable to control the detachment and reabsorption of lithium ions.
The initial capacity of the positive electrode plate is improved, the capacity climb problem is slowed down, and the battery circulation performance and energy density are improved.
Smart Images

Figure CN119674080A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a composite particle, a positive electrode sheet, a battery and an electrical device. Background Art
[0002] With the continuous development of energy storage technology, higher requirements are put forward for the capacity of battery cell pole pieces so that the battery has a higher energy density. Commonly, large-sized active particles are added to the battery cell pole pieces to increase the initial capacity of the battery cell pole pieces. However, large-sized active particles will bring about the problem of capacity climbing, which will affect the cycle performance of the battery. Therefore, it is necessary to provide an active material that can improve the capacity climbing phenomenon of the battery cell pole pieces at the beginning of the cycle while increasing the initial capacity of the battery cell pole pieces. Summary of the invention
[0003] In view of this, the present application provides a composite particle, a positive electrode plate, a battery and an electrical device. When the composite particle is applied to the battery, it can increase the initial capacity of the positive electrode plate, and can slow down the capacity climbing problem of the battery, and ultimately make the battery have a higher initial capacity and better cycle performance.
[0004] The present application provides a composite particle, which includes: a core, a first coating layer and a second coating layer, wherein the core includes lithium iron phosphate; the first coating layer is coated on the periphery of the core, and the first coating layer is a carbon layer; the second coating layer is coated on the periphery of the first coating layer, and the second coating layer is a metal oxide layer, and the ion conductivity of the second coating layer is variable.
[0005] Furthermore, when the composite particle is loaded with a first current, the second coating layer has a first ionic conductivity; when the composite particle is loaded with a second current, the second coating layer has a second ionic conductivity, wherein the first current is smaller than the second current, and the first ionic conductivity is greater than the second ionic conductivity.
[0006] Furthermore, as the current loaded on the composite particles gradually increases, the ionic conductivity of the second coating layer gradually decreases.
[0007] Furthermore, the second coating layer is selected from at least one of Al2O3, MgO, TiO2, SiO2, ZnO, SnO2 and ZrO2.
[0008] Furthermore, the median particle size D1 of the composite particles is in the range of 1 μm≤D1≤10 μm.
[0009] Furthermore, in the composite particles, the mass fraction A1 of the first coating layer is in the range of 0.5%≤A1≤4%.
[0010] Furthermore, in the composite particles, the mass fraction A2 of the second coating layer is in the range of 0.5%≤A2≤3%.
[0011] The present application provides a positive electrode plate, which includes: a positive electrode collector layer and a positive electrode material layer, wherein the positive electrode material layer is arranged on at least one surface of the positive electrode collector layer, and the positive electrode material layer includes active particles and composite particles provided in the present application, and the median particle size of the composite particles is larger than the median particle size of the active particles.
[0012] Furthermore, the median particle size of the composite particles is D1, and the median particle size of the active particles is D2, then the relationship is satisfied: 2≤D1 / D2≤15.
[0013] Furthermore, in the positive electrode material layer, the mass fraction A3 of the composite particles is in the range of 5%≤A3≤15%.
[0014] The present application provides a battery, which includes: a positive electrode plate, a diaphragm, a negative electrode plate and an electrolyte provided in the present application, wherein the diaphragm is arranged on one side of the positive electrode plate; the negative electrode plate is arranged on the side of the diaphragm away from the positive electrode plate; the electrolyte is used to infiltrate at least part of the positive electrode plate, the diaphragm and the negative electrode plate.
[0015] The present application provides an electrical device, which includes: a device body and a battery provided in the present application, wherein the battery supplies power to the device body.
[0016] In the composite particles provided in the present application, the core includes lithium iron phosphate, the first coating layer is coated on the periphery of the core, the first coating layer is a carbon layer, and the first coating layer can be used as a conductive layer to increase the conductivity of the composite particles and reduce the impedance of lithium ions escaping from the core and passing through the first coating layer. Even if the particle size of the core is large, the lithium iron phosphate in the core can still escape lithium ions and pass through the first coating layer, and escape from the positive electrode plate to replenish the lithium ions lost in the battery, which is beneficial to improve the initial capacity of the positive electrode plate. In addition, the composite particles also include a second coating layer, the second coating layer is coated on the periphery of the first coating layer, the second coating layer is a metal oxide layer, and the ion conductivity of the second coating layer is variable. In other words, the ion conductivity of the second coating layer can be adjusted to control the efficiency of lithium ions passing from the first coating layer to the second coating layer, and to control whether lithium ions can pass through the second coating layer. Specifically, at a certain stage of the battery charging process, the ionic conductivity of the second coating layer is relatively large, so that the lithium iron phosphate in the core can release lithium ions and pass through the first coating layer and the second coating layer in sequence to be transferred to the electrolyte and replenish the lithium ions consumed in the electrolyte, thereby realizing the lithium replenishment function to increase the initial capacity of the positive electrode plate. Further, during the battery discharging process, the ionic conductivity of the second coating layer is relatively small. In other words, it is difficult for the lithium ions in the electrolyte to pass through the second coating layer and return to the core. The lithium ions released from the lithium iron phosphate in the core will no longer return to the composite particles after being released. The lithium ions released from the lithium iron phosphate in the core do not participate in the charge and discharge cycle of the battery, and the composite particles serve as irreversible lithium replenishment materials. If the lithium ions released from the lithium iron phosphate in the core return to the composite particles, and the composite particles are large-sized particles, it may cause the problem of capacity climbing and reduce the cycle stability of the battery. The composite particles provided in the present application are in an inactivated state after the lithium ions are released. On the one hand, the capacity climbing problem can be avoided as much as possible to improve the cycle stability of the battery when the composite particles are applied to the battery; on the other hand, the impedance of the battery can be prevented from increasing due to the long path of lithium ions returning from the negative electrode to the composite particles, further improving the cycle performance of the battery. Furthermore, compared with the scheme of crushing large-sized composite particles, the composite particles of this embodiment have the second coating layer, which can avoid cracks in the composite particles, thereby avoiding the dissolution of iron in lithium iron phosphate from the cracks, and avoiding the increase of the internal resistance of the battery due to the cracks, and the composite particles have better performance. When the composite particles provided in this embodiment are applied to batteries, the composite particles can be used as irreversible lithium supplement materials to provide active lithium ions for the battery to increase the initial capacity of the positive electrode, and can slow down the capacity climbing problem of the battery, and ultimately make the battery have a higher energy density and better cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the implementation will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 A schematic diagram of the structure of a composite particle according to an embodiment of the present application;
[0019] Figure 2 A schematic cross-sectional structure diagram of a positive electrode sheet according to an embodiment of the present application;
[0020] Figure 3 A schematic cross-sectional structure diagram of a battery according to an embodiment of the present application;
[0021] Figure 4 This is a schematic diagram of the structure of an electrical device according to an embodiment of the present application;
[0022] Figure 5 This is a circuit block diagram of an electrical device according to an embodiment of the present application.
[0023] Description of reference numerals:
[0024] 100-composite particles, 110-core, 120-first coating layer, 130-second coating layer, 200-positive electrode plate, 210-positive electrode current collector layer, 220-positive electrode material layer, 221-active particles, 300-battery, 310-diaphragm, 320-negative electrode plate, 330-electrolyte, 400-electrical equipment, 410-equipment body. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0026] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.
[0027] Reference to "embodiment" or "implementation" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment or implementation may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0028] With the continuous development of energy storage technology, higher requirements are placed on the capacity of battery cell pole pieces so that the battery has a higher energy density. Commonly, large-sized active particles are added to the battery cell pole pieces to increase the initial capacity of the battery cell pole pieces. However, in large-sized active particles, the lithium ion diffusion path is longer and the diffusion resistance is greater, which can easily lead to a capacity increase in the battery cell pole pieces during the production process. If the increase is too obvious or lasts too long, it may affect the long-term cycle performance and reliability of the battery.
[0029] In the process of preparing the battery cell pole piece, the large-sized active particles in the battery cell pole piece are broken by increasing the rolling pressure of the battery cell pole piece to shorten the diffusion path of lithium ions. However, this method has two problems: first, it is difficult to crush the active particles by rolling, and excessive rolling pressure will cause the pole piece to stretch too much and break; second, after the large-sized particles are crushed, there is no carbon coating at the cracks, which will increase the impedance of the battery cell pole piece and reduce the initial capacity. In addition, the active materials in the active particles are easy to flow out from the cracks, resulting in accelerated cycle attenuation. For example, when the active particles are lithium iron phosphate particles, the iron in the lithium iron phosphate is easy to dissolve from the cracks. Therefore, it is necessary to provide an active material that improves the capacity climbing phenomenon of the battery cell pole piece at the beginning of the cycle while improving the initial capacity of the battery cell pole piece.
[0030] In the terminology of this application, "capacity climb phenomenon" refers to the phenomenon that the battery capacity gradually increases in the early stage of the cycle. When the battery cell pole piece includes large-sized active particles, the distance for lithium ions to diffuse from the surface of the particles to the inside of the particles is long, and the diffusion resistance is large, which may cause the battery to produce a large polarization phenomenon during the charge and discharge process. The polarization phenomenon will increase the degree to which the battery voltage deviates from the equilibrium potential, thereby affecting the performance of the battery in the early stage of the cycle. As the cycle progresses, the polarization phenomenon may gradually weaken, causing the battery capacity to gradually increase.
[0031] See also Figure 1The present application provides a composite particle 100, which includes: a core 110, a first coating layer 120 and a second coating layer 130, wherein the core 110 includes lithium iron phosphate; the first coating layer 120 is coated on the periphery of the core 110, and the first coating layer 120 is a carbon layer; the second coating layer 130 is coated on the periphery of the first coating layer 120, and the second coating layer 130 is a metal oxide layer, and the ionic conductivity of the second coating layer 130 is variable.
[0032] It can be understood that the core 110 , the first cladding layer 120 , and the second cladding layer 130 are arranged in sequence from the inside to the outside.
[0033] It can be understood that the ionic conductivity of the second coating layer 130 is variable, and thus under different external conditions, the second coating layer 130 has different ionic conductivity.
[0034] It can be understood that the composite particles 100 are applied to the positive electrode plate 200 and then assembled into the battery 300. When the battery 300 is a lithium-ion battery, the active ions in the battery 300 are lithium ions.
[0035] Optionally, the battery 300 further includes a separator 310 and a negative electrode sheet 320, wherein the positive electrode sheet 200, the separator 310 and the negative electrode sheet 320 are sequentially stacked, and during the charging process of the battery 300, lithium ions are deintercalated from the positive electrode sheet 200, and move to the negative electrode sheet 320 through the electrolyte 330 and then are embedded in the negative electrode sheet 320. During the discharging process of the battery 300, lithium ions are deintercalated from the negative electrode sheet 320, and move to the positive electrode sheet 200 through the electrolyte 330 and then are embedded in the positive electrode sheet 200.
[0036] In the composite particle 100 provided in this embodiment, the core 110 includes lithium iron phosphate, and the first coating layer 120 is coated on the periphery of the core 110, and the first coating layer 120 is a carbon layer. The first coating layer 120 can be used as a conductive layer to increase the conductivity of the composite particle 100 and reduce the impedance of lithium ions escaping from the core 110 and passing through the first coating layer 120. Even if the particle size of the core 110 is large, the lithium iron phosphate of the core 110 can still release lithium ions and pass through the first coating layer 120, and escape from the positive electrode plate 200 to replenish the lithium ions lost in the battery 300, which is beneficial to improve the initial capacity of the positive electrode plate 200. In addition, the composite particle 100 further includes a second coating layer 130, which is coated on the periphery of the first coating layer 120, and the second coating layer 130 is a metal oxide layer. The ionic conductivity of the second coating layer 130 is variable. In other words, the ionic conductivity of the second coating layer 130 can be adjusted to control the efficiency of lithium ions passing from the first coating layer 120 to the second coating layer 130, and to control whether lithium ions can pass through the second coating layer 130. Specifically, at a certain stage of the charging process of the battery 300, the ionic conductivity of the second coating layer 130 is relatively large, so that the lithium iron phosphate of the core 110 can release lithium ions and pass through the first coating layer 120 and the second coating layer 130 in sequence, so as to be transmitted to the electrolyte 330 and replenish the lithium ions consumed in the electrolyte 330, thereby realizing the lithium replenishment function to improve the initial capacity of the positive electrode plate 200. Furthermore, during the discharge process of the battery 300, the ionic conductivity of the second coating layer 130 is relatively small. In other words, it is difficult for the lithium ions in the electrolyte 330 to pass through the second coating layer 130 and return to the core 110. The lithium ions released from the lithium iron phosphate of the core 110 will no longer return to the composite particles 100 after being released. The lithium ions released from the lithium iron phosphate of the core 110 do not participate in the charge and discharge cycle of the battery 300. The composite particles 100 serve as irreversible lithium supplement materials. If the lithium ions released from the lithium iron phosphate of the core 110 return to the composite particles 100, and the composite particles 100 are large-sized particles, it may cause a capacity increase problem, reducing the cycle stability of the battery 300. The composite particles 100 provided in this embodiment are in an inactivated state after the lithium ions are released. On the one hand, the capacity climbing problem can be avoided as much as possible to improve the cycle stability of the battery 300 when the composite particles 100 are applied to the battery 300; on the other hand, it can also avoid the increase in the impedance of the battery 300 due to the long path of lithium ions returning from the negative electrode plate 320 to the composite particles 100, thereby further improving the cycle performance of the battery 300.Furthermore, compared to the solution of crushing the large-sized composite particles 100, the composite particles 100 of this embodiment have the second coating layer 130, which can prevent the composite particles 100 from cracking, thereby preventing the iron in the lithium iron phosphate from dissolving from the cracks, and can also prevent the internal resistance of the battery 300 from increasing due to the cracks. The composite particles 100 have good performance and a long service life. When the composite particles 100 provided in this embodiment are applied to the battery 300, the composite particles 100 can be used as an irreversible lithium supplement material to provide active lithium ions for the battery 300 to increase the initial capacity of the positive electrode plate 200, and can slow down the capacity climbing problem of the battery 300, and ultimately make the battery 300 have a higher energy density and better cycle performance.
[0037] In the terminology of the present application, “deactivated state” means that after the lithium ions released from the lithium iron phosphate of the core 110 are released from the composite particle 100 , the lithium ions lose the power to return to the interior of the composite particle 100 .
[0038] In the terminology of the present application, “the composite particle 100 serves as an irreversible lithium supplement material” means that the lithium ions released from the composite particle 100 no longer return to the interior of the composite particle 100 , and the lithium ions do not participate in the charge and discharge cycle of the battery 300 .
[0039] It can be understood that the second coating layer 130 coated on the periphery of the first coating layer 120 can also inhibit the attack of hydrogen fluoride in the electrolyte 330 on the composite particle 100 to inhibit the dissolution of iron in the lithium iron phosphate, thereby improving the performance of the composite particle 100.
[0040] Optionally, the second coating layer 130 is porous. In other words, the second coating layer 130 has a plurality of holes to facilitate the passage of lithium ions.
[0041] In some embodiments, when the composite particle 100 is loaded with a first current, the second coating layer 130 has a first ionic conductivity; when the composite particle 100 is loaded with a second current, the second coating layer 130 has a second ionic conductivity, wherein the first current is less than the second current, and the first ionic conductivity is greater than the second ionic conductivity.
[0042] It can be understood that when the composite particle 100 is loaded with different currents, the second coating layer 130 has different ionic conductivities. The current loaded by the composite particle 100 is the current loaded by the battery 300 when the composite particle 100 is applied to the battery 300.
[0043] In this embodiment, by controlling the magnitude of the current loaded on the composite particle 100, the ionic conductivity of the second coating layer 130 can be regulated, so as to regulate whether lithium ions can pass through the second coating layer 130. Specifically, when the composite particle 100 is applied to the battery 300 and the composite particle 100 is loaded with a small first current, the second coating layer 130 has a first ionic conductivity and the first ionic conductivity is large. If the battery 300 is in a charging state, the lithium iron phosphate of the core 110 can separate lithium ions and pass through the first coating layer 120 and the second coating layer 130 in sequence to be freed to the surface of the negative electrode plate 320 for lithium supplementation, thereby increasing the initial capacity of the positive electrode plate 200 and the energy density of the battery 300. When the composite particle 100 is loaded with a larger second current, the second coating layer 130 has a second ion conductivity and the second ion conductivity is larger, and it is difficult for lithium ions to enter the core 110 or escape from the core 110 through the second coating layer 130. If the battery 300 is in a discharge state, the lithium ions escaped from the core 110 can no longer pass through the second coating layer 130 and return to the inside of the composite particle 100, thereby preventing the lithium ions escaped from the composite particle 100 from participating in the charge and discharge cycle of the battery 300, thereby slowing down the capacity climbing phenomenon, and preventing the impedance of the battery 300 from increasing due to the long path of lithium ions returning from the negative electrode plate 320 to the composite particle 100. When the composite particle 100 of this embodiment is applied to the battery 300, it can not only improve the initial capacity of the positive electrode plate 200, but also make the battery 300 have both higher energy density and better cycle performance.
[0044] Optionally, in some embodiments, when the current of the first current satisfies the range of 0.02C to 0.05C, the composite particle 100 is in a low current environment, and the first ionic conductivity λ1 of the second coating layer 130 satisfies the range of: 10 -10 S / cm≤λ1≤10 -8 S / cm.
[0045] Optionally, in some embodiments, when the current of the first current satisfies the range of 0.2C to 1C or 0.2P to 1P, the composite particle 100 is in a high current environment, and the second ionic conductivity λ2 of the second coating layer 130 satisfies the range of: 10 -14 S / cm≤λ2<10 -10 S / cm.
[0046] It can be understood that a current of 0.05C means that during the charge and discharge process of the battery 300, the current is 0.05 times the nominal capacity of the battery 300; a current of 0.02C means that during the charge and discharge process of the battery 300, the current is 0.02 times the nominal capacity of the battery 300, and so on.
[0047] It can be understood that the current is 0.2P, where P is the product of the nominal capacity and the nominal voltage of the battery 300 .
[0048] It can be understood that during the charging process of the battery 300, the process can be divided into two stages. The first stage is a constant current charging stage, i.e., a capacity division stage, in which the battery 300 is first charged with a constant current until the voltage of the battery 300 reaches the set charging voltage. The current in this stage is usually between 0.2C and 1.0C. The second stage is a constant voltage charging stage, in which the battery 300 is close to being fully charged, and the current of the battery 300 is very small. The current in this stage is usually between 0.02C and 0.05C. The current in the first stage is the second current, and the composite particle 100 is in a large current environment; the current in the second stage is the first current, and the composite particle 100 is in a small current environment.
[0049] It can be understood that during the discharge process of the battery 300, the battery 300 is discharged at a constant current, the voltage of the battery 300 gradually decreases, the current at this stage is usually between 0.2C and 1.0C, the current at this stage is the second current, and the composite particles 100 are in a large current environment.
[0050] In some embodiments, as the current loaded on the composite particle 100 gradually increases, the ionic conductivity of the second coating layer 130 gradually decreases.
[0051] In this embodiment, when the composite particle 100 is applied to the battery 300, the magnitude of the current loaded by the composite particle 100 will change during the charge and discharge process of the battery 300, and as the current loaded by the composite particle 100 gradually increases, the ionic conductivity of the second coating layer 130 gradually decreases to control the efficiency of lithium ions separated from the lithium iron phosphate of the core 110 to escape from the composite particle 100. When the composite particle 100 is applied to the positive electrode plate 200 and assembled in the battery 300, during the charge and discharge process of the battery 300, the current loaded by the battery 300 can be regulated so that the composite particle 100 can be loaded with different currents, thereby realizing the use of the composite particle 100 as an irreversible lithium supplement material, while improving the initial capacity of the battery 300 and making the battery 300 have better cycle performance.
[0052] Specifically, in the process of charging the battery 300, the battery 300 is first charged with a constant current in the first stage, and the battery 300 is charged with a constant voltage in the second stage. At this time, the composite particle 100 is loaded with a first current, and the second coating layer 130 has a higher first ion conductivity. The lithium iron phosphate in the core 110 can release lithium ions and pass through the first coating layer 120 and the second coating layer 130 in turn to escape from the composite particle 100, and be supplemented to the negative electrode plate 320 through the electrolyte 330 to supplement the lithium ions consumed in the electrolyte 330, thereby achieving an increase in the initial capacity of the positive electrode plate 200. Furthermore, during the discharge process of the battery 300, the battery 300 does not have a stage of low current discharge, then the composite particle 100 is loaded with a second current, and the second coating layer 130 has a lower second ion conductivity, and the lithium ions released from the core 110 are difficult to pass through the second coating layer 130 to return to the inside of the composite particle 100, thereby slowing down the occurrence of the capacity climbing phenomenon, and avoiding the increase in the impedance of the battery 300 due to the long path of the lithium ions returning from the negative electrode plate 320 to the composite particle 100. When the composite particle 100 of this embodiment is applied to the battery 300, it can not only improve the initial capacity of the positive electrode plate 200, but also make the battery 300 have both higher energy density and better cycle performance. In addition, the method for regulating the ionic conductivity of the second coating layer 130 is simple and easy to implement.
[0053] In some embodiments, the second coating layer 130 is selected from at least one of Al2O3, MgO, TiO2, SiO2, ZnO, SnO2 and ZrO2.
[0054] It can be understood that, in the terms of the present application, "at least one" means one or more, and "a plurality of" means greater than or equal to two.
[0055] In this embodiment, when the second coating layer 130 is selected from at least one of Al2O3, MgO, TiO2, SiO2, ZnO, SnO2 and ZrO2, the second coating layer 130 is electrochemically inert, and the ionic conductivity of the second coating layer 130 is variable. When the composite particle 100 is applied to the battery 300 and during the charging process of the battery 300, when the composite particle 100 is loaded with a first current, the composite particle 100 has a large first ionic conductivity, and the lithium iron phosphate in the core 110 can release lithium ions and pass through the first coating layer 120 and the second coating layer 130 in sequence, so as to escape from the composite particle 100 and replenish the lithium ions consumed in the electrolyte 330, thereby improving the initial capacity of the positive electrode plate 200. During the discharge process of the battery 300, the battery 300 does not have a small current discharge stage. The composite particle 100 is loaded with a second current, and the second ion conductivity of the second coating layer 130 is low. It is difficult for lithium ions to enter the composite particle 100 again, so that the lithium iron phosphate in the composite particle 100 can be used as an irreversible lithium supplement material, thereby slowing down the capacity climb of the battery 300, so that the battery 300 has better cycle stability.
[0056] It can be understood that when the second coating layer 130 is selected from Al2O3, the second coating layer 130 forms electronic energy levels due to its local defects, vacancies and other structures, so that electrons in the local area can be freely transmitted at the defects, so that the second coating layer 130 has certain ion conductive properties.
[0057] In some embodiments, the median particle size D1 of the composite particles 100 is in the range of 1 μm≤D1≤10 μm.
[0058] Specifically, the median particle size D1 of the composite particles 100 can be, but is not limited to, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2 μm, 2.3 μm, 2.8 μm, 3 μm, 3.2 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.6 μm, 6 μm, 6.5 μm, 7 μm, 8 μm, 9 μm, 9.5 μm and 10 μm, etc.
[0059] When the median particle size D1 of the composite particles 100 satisfies the range of 1μm≤D1≤10μm, the median particle size of the composite particles 100 is within a reasonable range. On the one hand, when the composite particles 100 are applied to the positive electrode sheet 200, the composite particles 100 can give full play to the role of large particles to improve the compaction density of the positive electrode sheet 200, thereby improving the initial capacity of the positive electrode sheet 200. On the other hand, the composite particle 100 includes a core 110, a first coating layer 120 and a second coating layer 130. The first coating layer 120 can improve the conductivity of the large-sized composite particle 100. The second coating layer 130 can control the ionic conductivity to achieve control of lithium ions passing through the second coating layer 130 from the core 110, but cannot return to the interior of the composite particle 100, so that the lithium iron phosphate of the core 110 can replenish the lithium ions consumed by the electrolyte 330 and the lithium ions released by the core 110 do not participate in the charge and discharge cycle, thereby alleviating the capacity climb problem caused by the large-sized composite particle 100 when applied to the positive electrode plate 200. The composite particle 100 has good performance in use. When the median particle size of the composite particle 100 is too large, correspondingly, the particle size of the core 110 is too large, then even if the first coating layer 120 is provided on the periphery of the core 110, it is difficult to improve the conductivity of the composite particle 100, and the path for the lithium ions released by the lithium iron phosphate of the core 110 to escape is too long. When the composite particle 100 is loaded with the first current, even if the second coating layer 130 has a large first ion conductivity, the lithium ions released by the lithium iron phosphate of the core 110 are still difficult to escape and exert the lithium supplement performance. Therefore, when the composite particle 100 is applied to the positive electrode sheet 200, the initial capacity of the positive electrode sheet 200 is low. When the median particle size of the composite particle 100 is too small, when the composite particle 100 is applied to the positive electrode sheet 200, it is difficult to improve the compaction density and initial capacity of the positive electrode sheet 200, thereby it is difficult to improve the energy density of the battery 300, and the composite particle 100 has a small degree of improvement in the cycle performance of the battery 300.
[0060] Preferably, the median particle size D1 of the composite particles 100 is in the range of 1.2 μm ≤ D1 ≤ 5 μm. Specifically, the median particle size D1 of the composite particles 100 may be, but is not limited to, 1.2 μm, 1.5 μm, 1.8 μm, 2 μm, 2.3 μm, 2.8 μm, 3 μm, 3.2 μm, 3.5 μm, 4 μm, 4.5 μm, or 5 μm.
[0061] In some embodiments, in the composite particle 100 , the mass fraction A1 of the first coating layer 120 is in the range of 0.5%≤A1≤4%.
[0062] It can be understood that, in the composite particle 100 , the mass fraction of the first coating layer 120 is the ratio of the mass of the first coating layer 120 to the mass of the composite particle 100 .
[0063] Specifically, the mass fraction A1 of the first coating layer 120 can be, but is not limited to, 0.5%, 0.6%, 0.88%, 1%, 1.2%, 1.35%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.1%, 2.3%, 2.5%, 2.7%, 3%, 3.2%, 3.4%, 3.5%, 3.8% and 4%, etc.
[0064] In the composite particle 100 provided in this embodiment, the first coating layer 120 is a carbon coating layer, and the first coating layer 120 is directly coated on the periphery of the core 110. The first coating layer 120 enables the composite particle 100 to have better conductivity, which facilitates the lithium ions released by the lithium iron phosphate of the core 110 to pass through the first coating layer 120 and escape from the composite particle 100 to exert the lithium replenishment performance. When the mass fraction A1 of the first coating layer 120 satisfies the range of 0.5%≤A1≤4%, the mass fraction of the first coating layer 120 is within a reasonable range, and the first coating layer 120 can not only improve the conductivity of the composite particle 100, but also be uniformly coated on the outer periphery of the core 110 to prevent the lithium ions of the lithium iron phosphate in the core 110 from escaping, and to prevent the first coating layer 120 from cracking and causing the iron in the lithium iron phosphate to dissolve, so that the composite particle 100 can exert lithium replenishment performance and have a longer service life to improve the initial capacity of the positive electrode plate 200. When the mass fraction of the first coating layer 120 is too large, in other words, the thickness of the first coating layer 120 is too thick, the carbon in the first coating layer 120 is difficult to be uniformly coated on the surface of the core 110, and the specific surface area of the carbon in the first coating layer 120 is too small, which increases the difficulty and impedance of the lithium ions released from the lithium iron phosphate in the core 110 passing through the first coating layer 120, so that the composite particle 100 is difficult to play the lithium supplement performance, and finally reduces the initial capacity of the positive electrode plate 200. When the mass fraction of the first coating layer 120 is too small, the first coating layer 120 is difficult to fully improve the conductivity of the composite particle 100, increases the difficulty and impedance of the lithium ions released from the lithium iron phosphate in the core 110 passing through the first coating layer 120, affects the transmission performance of lithium ions, and when the composite particle 100 is applied to the battery 300, the internal resistance of the battery 300 is increased, thereby reducing the cycle performance of the battery 300.
[0065] Preferably, the mass fraction A1 of the first coating layer 120 is in the range of 0.5%≤A1≤2%. Specifically, the mass fraction A1 of the first coating layer 120 may be, but is not limited to, 0.5%, 0.6%, 0.88%, 1%, 1.2%, 1.35%, 1.4%, 1.5%, 1.6%, 1.8% and 2%.
[0066] In some embodiments, the thickness h1 of the first cladding layer 120 is in the range of 2 nm≤h1≤5 nm.
[0067] Specifically, the thickness h1 of the first cladding layer 120 may be, but is not limited to, 2 nm, 2.1 nm, 2.3 nm, 2.5 nm, 3 nm, 3.3 nm, 3.6 nm, 3.8 nm, 4 nm, 4.2 nm, 4.8 nm, 5 nm, etc.
[0068] It can be understood that the thickness of the first coating layer 120 is at the nanometer level.
[0069] In this embodiment, the particle size D1 of the composite particle 100 satisfies the range of 1μm≤D1≤10μm, the composite particle 100 is a large-sized active material, and the thickness of the first coating layer 120 is nanometer level, so as to coat the outer periphery of the core 110, so that the volume of the core 110 in the composite particle 100 accounts for a larger proportion, so that the composite particle 100 can provide more active lithium ions for the battery 300 to make up for the lithium ions consumed in the electrolyte 330, so that the positive electrode plate 200 has a larger initial capacity. When the thickness h1 of the first coating layer 120 satisfies the range of 2nm≤h1≤5nm, the thickness of the first coating layer 120 is within a reasonable range, and the first coating layer 120 can not only improve the conductivity of the composite particle 100, but also be uniformly coated on the outer periphery of the core 110 to prevent the lithium ions of the lithium iron phosphate of the core 110 from escaping, and to prevent the first coating layer 120 from cracking and causing the iron in the lithium iron phosphate to dissolve, so that the composite particle 100 can exert lithium replenishment performance and have a longer service life to improve the initial capacity of the positive electrode plate 200. When the thickness of the first coating layer 120 is too large, it is difficult for the carbon in the first coating layer 120 to be uniformly coated on the surface of the core 110, and the specific surface area of the carbon in the first coating layer 120 is too small, which increases the difficulty and impedance of the lithium ions released from the lithium iron phosphate in the core 110 to pass through the first coating layer 120, thereby making it difficult for the composite particle 100 to exert its lithium replenishment performance, and ultimately reducing the initial capacity of the positive electrode sheet 200. Furthermore, the first coating layer 120 occupies too much volume of the composite particle 100, which will lead to a reduction in the volume share of the core 110, thereby reducing the amount of lithium ions released by the core 110, and ultimately reducing the initial capacity of the positive electrode sheet 200. When the thickness of the first coating layer 120 is too small, it is difficult for the first coating layer 120 to fully improve the conductivity of the composite particle 100, which increases the difficulty and impedance of lithium ions released from the lithium iron phosphate in the core 110 to pass through the first coating layer 120, affecting the transmission performance of lithium ions. When the composite particle 100 is applied to the battery 300, the internal resistance of the battery 300 is increased, thereby reducing the cycle performance of the battery 300.
[0070] In some embodiments, in the composite particle 100 , the mass fraction A2 of the second coating layer 130 is in the range of 0.5%≤A2≤3%.
[0071] It can be understood that, in the composite particle 100 , the mass fraction of the second coating layer 130 is the ratio of the mass of the second coating layer 130 to the mass of the composite particle 100 .
[0072] Specifically, the mass fraction A2 of the second coating layer 130 can be, but is not limited to, 0.5%, 0.6%, 0.88%, 1%, 1.2%, 1.35%, 1.4%, 1.6%, 1.8%, 2%, 2.1%, 2.3%, 2.5%, 2.7% and 3%, etc.
[0073] In the composite particle 100 provided in this embodiment, the mass fraction of the second coating layer 130 also has a certain influence on the ionic conductivity of the second coating layer 130 . Specifically, when the mass fraction A2 of the second coating layer 130 satisfies the range of 0.5%≤A2≤3%, the mass fraction of the second coating layer 130 is within a reasonable range, and the ionic conductivity of the second coating layer 130 is also within a reasonable range, so that when the composite particle 100 is in a small current environment and loaded with a first current, the second coating layer 130 has a larger first ionic conductivity, and the lithium iron phosphate of the inner core 110 can separate lithium ions and allow the lithium ions to escape. When the composite particle 100 is in a large current environment and loaded with a second current, the second coating layer 130 has a smaller second ionic conductivity, and the lithium ions escaped from the lithium iron phosphate of the composite particle 100 cannot return to the composite particle 100, so that the lithium iron phosphate in the composite particle 100 can be used as an irreversible lithium supplement material to slow down the capacity climb problem caused by the application of large-sized active materials in the battery 300, and ultimately enable the battery 300 to have a higher initial capacity, energy density and better cycle performance. When the mass fraction of the second coating layer 130 is too large, the content of the second coating layer 130 in the composite particle 100 is too much. When the composite particle 100 is applied to the battery 300 and the battery 300 is in a charging state, even if the composite particle 100 is loaded with a first current, the lithium ions released from the lithium iron phosphate in the core 110 are difficult to pass through the second coating layer 130. It is difficult for the composite particle 100 to release lithium ions, so that the composite particle 100 cannot provide lithium ions for the battery 300, thereby reducing the initial capacity of the positive electrode plate 200, thereby reducing the energy density and initial capacity of the battery 300. When the mass fraction of the second coating layer 130 is too small, firstly, it is difficult for the second coating layer 130 to completely and evenly coat the periphery of the first coating layer 120, and a part of the first coating layer 120 is still directly exposed to the electrolyte 330. When the battery 300 is in the discharge process, the lithium ions released from the composite particles 100 can still pass through the second coating layer 130 and the first coating layer 120 and enter the core 110. Secondly, the smaller the mass fraction of the second coating layer 130, the smaller the second coating layer 130. 130 has insufficient passivation ability for large currents. When the battery 300 is in the discharge process, the composite particle 100 is in a large current environment and loaded with a second current, the ionic conductivity of the second coating layer 130 is relatively high, which may also cause the lithium ions released from the composite particle 100 to still pass through the second coating layer 130 and the first coating layer 120 and enter the core 110. In other words, the lithium ions released from the composite particle 100 participate in the charge and discharge cycle of the battery 300, and the composite particle 100 cannot be used as an irreversible lithium supplement material.In the process of the lithium ions released from the composite particles 100 returning from the negative electrode pole piece 320 to the core 110, on the one hand, it may cause the capacity climbing problem of the battery 300, thereby reducing the cycle stability of the battery 300; on the other hand, the path for the ions to return from the negative electrode pole piece 320 to the core 110 is too long, which will increase the impedance of the battery 300, thereby reducing the cycle performance of the battery 300.
[0074] Preferably, the mass fraction A2 of the second coating layer 130 is in the range of 0.5%≤A2≤2%. Specifically, the mass fraction A2 of the second coating layer 130 may be, but is not limited to, 0.5%, 0.6%, 0.88%, 1%, 1.2%, 1.35%, 1.4%, 1.6%, 1.8% and 2%.
[0075] In some embodiments, the thickness h2 of the second cladding layer 130 is in the range of 2 nm≤h2≤8 nm.
[0076] In this embodiment, when the thickness h2 of the second coating layer 130 satisfies the range of 2nm≤h2≤8nm, the thickness of the second coating layer 130 is within a reasonable range, and the ionic conductivity of the second coating layer 130 is also within a reasonable range, so that when the composite particle 100 is in a small current environment and loaded with a first current, the second coating layer 130 has a larger first ionic conductivity, and the lithium iron phosphate of the inner core 110 can separate lithium ions and allow the lithium ions to escape. When the composite particle 100 is in a large current environment and loaded with a second current, the second coating layer 130 has a smaller second ionic conductivity, and the lithium ions escaped from the lithium iron phosphate of the composite particle 100 cannot return to the composite particle 100, so that the lithium iron phosphate in the composite particle 100 can be used as an irreversible lithium supplement material to slow down the capacity climb problem caused by the application of large-sized active materials in the battery 300, and ultimately enable the battery 300 to have a higher initial capacity, energy density and better cycle performance. When the thickness of the second coating layer 130 is too large, the content of the second coating layer 130 in the composite particle 100 is too much. When the composite particle 100 is applied to the battery 300 and the battery 300 is in a charging state, even if the composite particle 100 is loaded with a first current, the lithium ions released from the lithium iron phosphate in the core 110 are difficult to pass through the second coating layer 130. It is difficult for the composite particle 100 to release lithium ions, so that the composite particle 100 cannot provide lithium ions for the battery 300, thereby reducing the initial capacity of the positive electrode plate 200, thereby reducing the energy density and initial capacity of the battery 300. When the thickness of the second coating layer 130 is too small, firstly, it is difficult for the second coating layer 130 to completely and evenly coat the periphery of the first coating layer 120, and a part of the first coating layer 120 is still directly exposed to the electrolyte 330. When the battery 300 is in the discharge process, the lithium ions released from the composite particles 100 can still pass through the second coating layer 130 and the first coating layer 120 and enter the core 110. Secondly, the smaller the mass fraction of the second coating layer 130, the smaller the second coating layer 1 30 has insufficient passivation ability for large currents. When the battery 300 is in the discharge process, the composite particle 100 is in a large current environment and loaded with a second current, the ionic conductivity of the second coating layer 130 is relatively high, which may also cause the lithium ions released from the composite particle 100 to still pass through the second coating layer 130 and the first coating layer 120 and enter the core 110. In other words, the lithium ions released from the composite particle 100 participate in the charge and discharge cycle of the battery 300, and the composite particle 100 cannot be used as an irreversible lithium supplement material.In the process of the lithium ions released from the composite particles 100 returning from the negative electrode pole piece 320 to the core 110, on the one hand, it may cause the capacity climbing problem of the battery 300, thereby reducing the cycle stability of the battery 300; on the other hand, the path for the ions to return from the negative electrode pole piece 320 to the core 110 is too long, which will increase the impedance of the battery 300, thereby reducing the cycle performance of the battery 300.
[0077] It can be understood that the thickness of the second coating layer 130 is in the nanometer level.
[0078] See also Figure 2 The present application provides a positive electrode plate 200, which includes: a positive electrode collector layer 210 and a positive electrode material layer 220, wherein the positive electrode material layer 220 is arranged on at least one surface of the positive electrode collector layer 210, and the positive electrode material layer 220 includes active particles 221 and composite particles 100 provided in the present application, and the median particle size of the composite particles 100 is larger than the median particle size of the active particles 221.
[0079] It can be understood that in the positive electrode material layer 220 , the number of the active particles 221 is plural, the number of the composite particles 100 is plural, and the plural active particles 221 and the plural composite particles 100 are mixed and dispersed in the positive electrode material layer 220 .
[0080] Optionally, in some embodiments, the positive electrode material layer 220 is disposed on one surface of the positive electrode current collector layer 210 ; in other embodiments, the positive electrode material layer 220 is disposed on two opposite surfaces of the positive electrode current collector layer 210 .
[0081] It can be understood that the active particles 221 and the composite particles 100 are both positive electrode active materials. In some possible embodiments, the active particles 221 include lithium iron phosphate.
[0082] In this embodiment, the positive electrode material layer 220 includes active particles 221 and the composite particles 100 of the present application, and the active particles 221 and the composite particles 100 are dispersed in the positive electrode material layer 220, and the median particle size of the composite particles 100 is larger than the median particle size of the active particles 221. Then, in the positive electrode material layer 220, the composite particles 100 serve as large-sized positive electrode active materials, and the active particles 221 serve as small-sized positive electrode active materials. The active particles 221 can fill the gaps between multiple composite particles 100, so that the positive electrode material layer 220 has a larger compaction density, thereby improving the initial capacity of the positive electrode plate 200. Furthermore, the composite particle 100 includes a core 110, a first coating layer 120 and a second coating layer 130, and the first coating layer 120 can improve the conductivity of the composite particle 100, and the second coating layer 130 can make the lithium iron phosphate of the core 110 release lithium ions and the released lithium ions do not participate in the charge and discharge cycle of the battery 300, thereby alleviating the capacity climbing problem caused by the application of large-sized positive electrode active materials to the positive electrode plate 200, so that when the positive electrode plate 200 is applied to the battery 300, the battery 300 has both a higher initial capacity and better cycle performance.
[0083] In some embodiments, the median particle size of the composite particles 100 is D1, and the median particle size of the active particles 221 is D2, and the relationship is satisfied: 2≤D1 / D2≤15.
[0084] Specifically, the value of D1 / D2 can be, but is not limited to, 2, 3, 3.5, 4, 4.5, 5, 6, 7, 8, 9, 9.5, 10, 11, 11.5, 12, 12.4, 13, 14 and 15, etc.
[0085] In the positive electrode material layer 220 provided in this embodiment, when the median particle size D1 of the composite particles 100 and the median particle size D2 of the active particles 221 satisfy the range of 2≤D1 / D2≤15, the median particle size of the composite particles 100 and the median particle size of the active particles 221 are both within a reasonable range. The composite particles 100, as large-sized positive electrode active materials, can provide more lithium ions for the positive electrode material layer 220. The active particles 221, as small-sized positive electrode active materials, can fill the gaps between the plurality of composite particles 100, so that the positive electrode plate 200 has a higher compaction density and a higher initial capacity. When the positive electrode plate 200 is applied to a battery 300, the battery 300 has a higher initial capacity, energy density and better cycle performance. When the value of D1 / D2 is too large, the median particle size of the composite particle 100 is too large or the median particle size of the active particle 221 is too small. If the median particle size of the composite particle 100 is too large, correspondingly, the particle size of the core 110 is too large, and the path for the lithium ions released by the lithium iron phosphate of the core 110 to escape is too long. When the composite particle 100 is loaded with the first current, even if the second coating layer 130 has a larger first ion conductivity, the lithium ions released by the lithium iron phosphate of the core 110 are still difficult to escape and play a lithium supplement performance. Therefore, when the composite particle 100 is applied to the positive electrode sheet 200, the initial capacity of the positive electrode sheet 200 is low. If the median particle size of the active particle 221 is too small, correspondingly, the specific surface area of the active particle 221 is too large, which may lead to an increase in the side reactions of the active particle 221 with the electrolyte 330, thereby reducing the cycle performance of the battery 300. When the value of D1 / D2 is too small, the median particle size of the composite particle 100 is too small or the median particle size of the active particle 221 is too large, and the composite particle 100 and the active particle 221 are difficult to fully utilize the space of the positive electrode material layer 220, so that the compaction density and energy density of the positive electrode plate 200 are relatively low. When the median particle size of the composite particle 100 is too small, the capacity of the composite particle 100 for lithium supplementation will be higher, which can alleviate the problem of low gram capacity of the active particle 221 to a certain extent, but the improvement is small. If the median particle size of the active particle 221 is too large, then correspondingly, the gram capacity of the active particle 221 is low, which will also lead to a low initial capacity of the battery 300. In addition, the larger-sized active particles 221 have poor kinetic performance during the cycle, and the active particles 221 are prone to decay and cracks, which makes the cycle performance of the battery 300 poor.
[0086] It can be understood that the powder resistivity of the composite particles 100 is 5 to 50 times that of the active particles 221. Therefore, in the active material layer, the mass fraction of the composite particles 100 should not be too large.
[0087] Preferably, the range of D1 / D2 is: 5≤D1 / D2≤10.
[0088] In some embodiments, in the positive electrode material layer 220 , the mass fraction A3 of the composite particles 100 is in the range of 5%≤A3≤15%.
[0089] It can be understood that in the positive electrode material layer 220 , the mass fraction of the composite particles 100 is the ratio of the sum of the masses of the plurality of composite particles 100 to the mass of the positive electrode material layer 220 .
[0090] Specifically, in the positive electrode material layer 220, the mass fraction A3 of the composite particles 100 can be but is not limited to 5%, 5.5%, 6%, 7%, 8%, 8.6%, 9%, 10%, 10.2%, 11%, 11.7%, 12%, 12.6%, 13%, 13.5%, 14%, 14.6% and 15%, etc.
[0091] In the positive electrode sheet 200 provided in this embodiment, when the mass fraction A3 of the composite particles 100 satisfies the range of 5%≤A3≤15%, the mass fraction A3 of the composite particles 100 is within a reasonable range. On the one hand, the composite particles 100 and the active particles 221 cooperate with each other to make full use of the space of the positive electrode material layer 220, so that the positive electrode sheet 200 has a higher compaction density; on the other hand, the core 110 of the composite particles 100 can release lithium ions to timely replenish the lithium ions consumed in the electrolyte 330. The composite particles 100 can be used as an irreversible lithium supplement material, which can improve the initial capacity of the positive electrode sheet 200 while slowing down the capacity climbing phenomenon of the battery 300, so that the battery 300 has both a higher initial capacity and a higher energy density, and the battery 300 has better cycle performance. When the mass fraction A3 of the composite particles 100 is too large, the proportion of the composite particles 100 in the positive electrode material layer 220 is too large, and the mass proportion of the active particles 221 is too small. After the lithium ions in the composite particles 100 are released, they no longer return to the composite particles 100, that is, the composite particles 100, as irreversible lithium supplement materials, do not participate in the charge and discharge cycle of the battery 300. If the mass fraction of the composite particles 100 is too large, the initial capacity of the battery 300 is low, and the cycle performance of the battery 300 decreases as the active lithium ions in the electrolyte 330 are consumed. When the mass fraction A3 of the composite particles 100 is too small, the mass content of the active particles 221 is too large, and the compaction density of the positive electrode plate 200 is small, and the content of lithium ions released from the composite particles 100 is small, and it is difficult to supplement the lithium ions consumed in the electrolyte 330, so that although the positive electrode plate 200 has a high initial capacity, the cycle performance of the battery 300 is poor.
[0092] See also Figure 3 The present application provides a battery 300, which includes: a positive electrode sheet 200, a diaphragm 310, a negative electrode sheet 320 and an electrolyte 330 provided in the present application, wherein the diaphragm 310 is arranged on one side of the positive electrode sheet 200; the negative electrode sheet 320 is arranged on the side of the diaphragm 310 away from the positive electrode sheet 200; the electrolyte 330 is used to infiltrate at least part of the positive electrode sheet 200, the diaphragm 310 and the negative electrode sheet 320.
[0093] Optionally, in some embodiments, the battery 300 is a lithium-ion battery, and the battery 300 contains lithium ions.
[0094] It can be understood that the positive electrode sheet 200 , the separator 310 and the negative electrode sheet 320 are stacked in sequence, and the positive electrode sheet 200 , the separator 310 and the negative electrode sheet 320 form an electrode assembly.
[0095] It can be understood that the preparation process of the battery 300 is divided into a formation process and a capacity division process. In the early stage of the formation process, there is a small current to form an interface film on the surface of the negative electrode plate 320, and then it is charged to a specified SOC, followed by a capacity division process. The capacity division process of the battery 300 is a CCCV process, that is, constant current and constant voltage charging. This process can be divided into two stages. The first stage is a constant current charging stage, that is, a capacity division stage. The battery 300 is first charged with a constant current until the voltage of the battery 300 reaches the set charging voltage. The current in this stage is usually between 0.2C and 1.0C; the second stage is a constant voltage charging stage. At this time, the battery 300 is close to full charge, and the current of the battery 300 is very small. The current in this stage is usually between 0.02C and 0.05C. Among them, the current in the first stage is the second current, and the composite particle 100 is in a large current environment; the current in the second stage is the first current, and the composite particle 100 is in a small current environment.
[0096] It can be understood that, in the terminology of the present application, “formation” refers to the process of charging the battery 300 after liquid injection with a small current; “SOC” refers to the charging progress of the battery 300.
[0097] In the battery 300 provided in this embodiment, the electrolyte 330 is used to infiltrate at least a portion of the electrode assembly to achieve the transmission of lithium ions between the electrolyte 330 and the electrode assembly. In particular, the battery 300 includes the positive electrode plate 200 provided in this application, and the positive electrode material layer 220 of the positive electrode plate 200 includes the composite particles 100 provided in this application, and the composite particles 100 are large-sized positive electrode active materials, which cooperate with the active particles 221 to make the positive electrode plate 200 have a larger compaction density. At the same time, the composite particles 100 can be used as an irreversible lithium supplement material to release lithium ions and supplement the lithium ions lost in the electrolyte 330 when the first current is loaded, so that the positive electrode plate 200 has a higher initial capacity. Furthermore, the composite particle 100 is provided with a second coating layer 130 with variable ion conductivity to prevent the lithium ions released from the core 110 from returning to the core 110, slowing down the capacity increase phenomenon, and preventing the impedance of the battery 300 from increasing due to the long path of the lithium ions returning from the negative electrode plate 320 to the composite particle 100. The battery 300 provided in this embodiment has both high energy density and initial capacity, and has good cycle performance.
[0098] Optionally, in the battery 300, in the constant current charging stage of the battery 300, the current of the battery 300 is I1, and in the constant voltage charging stage of the battery 300, the current of the battery 300 is I2, and I2 is constantly changing, then the relationship is satisfied: 4≤I1 / I2≤50.
[0099] It can be understood that in the constant current charging stage of the battery 300, the current of the battery 300 is I1, and the magnitude of the second current loaded by the composite particles 100 is I1; in the constant voltage charging stage of the battery 300, the current of the battery 300 is I2, and the magnitude of the first current loaded by the composite particles 100 is I2.
[0100] Specifically, the value of I1 / I2 can be but is not limited to 4, 5, 6, 8, 10, 12, 14, 16, 17, 18, 20, 22, 25, 28, 30, 32, 35, 36, 38, 40, 42, 43, 45, 47, 49 and 50, etc.
[0101] Optionally, during the discharge phase of the battery 300 , the current of the battery 300 is I3 , and the relationship is satisfied: 4≤I3 / I2≤50.
[0102] It can be understood that, during the discharge stage of the battery 300 , the current of the battery 300 is I3, and the magnitude of the second current loaded on the composite particles 100 is I3.
[0103] Specifically, the value of I3 / I2 can be but is not limited to 4, 5, 6, 8, 10, 12, 14, 16, 17, 18, 20, 22, 25, 28, 30, 32, 35, 36, 38, 40, 42, 43, 45, 47, 49 and 50, etc.
[0104] Optionally, in the negative electrode plate 320, the negative electrode plate 320 includes a negative positive electrode current collector layer 210 and a negative electrode material layer, the negative electrode material layer is disposed on the surface of the negative electrode current collector layer, and the negative electrode material layer includes a negative electrode active material.
[0105] The technical solution of this application is further introduced in the following with multiple embodiments:
[0106] Example 1 to Example 11, Comparative Example 1:
[0107] 1. Preparation of positive electrode sheet 200:
[0108] (1) Preparation of composite particles 100:
[0109] Step 1: FePO4 (specific surface area BET range: 8m 2 / g to 12m 2 / g), lithium carbonate, glucose, TiO2, etc. are added into a homogenizing tank in a certain proportion, and then deionized water is added, and the solid content is maintained at 45% to 55%; then the powder is loaded into a graphite sagger after coarse grinding, fine grinding, and spray drying, the sintering temperature is 600°C to 770°C, the sintering time is 8h to 16h, and then the first intermediate particles are obtained by air flow pulverization;
[0110] Step 2: FePO4 (specific surface area BET range: 4m 2 / g to 8m 2 / g), lithium carbonate, glucose, TiO2, Al2O3, etc. are added into a homogenizing tank in a certain proportion, and then deionized water is added, and the solid content is maintained at 45% to 55%; then the powder is loaded into a graphite sagger after coarse grinding, fine grinding, and spray drying, and the sintering temperature is 700°C to 810°C, the sintering time is 8h to 16h, and then the second intermediate particles are obtained by air flow pulverization; the average size of the second intermediate particles is 2μm, and the carbon content is 1.0%;
[0111] Step 3: Take the first intermediate particles and the second intermediate particles in a weight ratio of 90%:10%, as well as glucose and polyethylene glycol with an average molecular weight of 2000, and add them into a homogenizing tank, and then add deionized water, and keep the solid content at 45% to 55%; then after sufficient mixing and spray drying, the powder is loaded into a graphite sagger, the sintering temperature is 750°C to 810°C, the sintering time is 8h to 16h, and then air flow crushing, demagnetization, packaging and other processes are performed to obtain the composite particles 100 of Examples 1 to 11 and Comparative Example 1.
[0112] The composite particle 100 includes a core 110, a first coating layer 120 and a second coating layer 130, wherein the core 110 includes lithium iron phosphate; the first coating layer 120 is coated on the periphery of the core 110, and the first coating layer 120 is a carbon layer; the second coating layer 130 is coated on the periphery of the first coating layer 120, and the second coating layer 130 is a metal oxide layer, and the ion conductivity of the second coating layer 130 is variable. The second coating layer 130 of the composite particle 100 in Examples 1 to 11 and Comparative Example 1 is Al2O3 as an example, which should not be understood as limiting the type of the second coating layer 130.
[0113] Among them, the values of the median particle size D1 of the composite particles 100 of Examples 1 to 11 and Comparative Example 1, the values of the mass fraction A1 of the first coating layer 120, the values of the mass fraction A2 of the second coating layer 130, and the ratio of the median particle size D1 of the composite particles 100 to the median particle size D2 of the active particles 221 are shown in Table 1.
[0114] Among them, the value of the mass fraction A1 of the first coating layer 120 and the value of the mass fraction A2 of the second coating layer 130 are measured by a ratio determination method, which is as follows: an energy dispersive spectrometer (EDS) is used to test the carbon content and Al2O3 content on the surface of the secondary particle section and inside the secondary particles, and the ratio is calculated. Specifically, the point scanning working mode of EDS is used to evenly select 5 points in the internal area on the secondary particle section, and the instrument automatically analyzes the carbon content and Al2O3 content of each point, and takes the average value to obtain the carbon content and Al2O3 content inside the particle; similarly, 5 points in the surface area are selected on the secondary particle section, and the instrument automatically analyzes the carbon content and Al2O3 content of each point, and takes the average value to obtain the carbon content and Al2O3 on the surface of the secondary particles. Among them, the method for obtaining the cross-section of the secondary particles is: burying the composite particles in resin, using a cross-section polisher, and cutting the composite particles buried in the resin by argon sputtering to expose the secondary particle cross-section of the composite particles. The internal region of the secondary particle refers to the region within 60% of the center of the secondary particle, and the surface region of the secondary particle refers to the region outside 60% of the center of the secondary particle.
[0115] (2) Preparation of positive electrode sheet 200:
[0116] The composite particles 100, active particles 221 lithium iron phosphate (LiFePO4), conductive carbon black (Super-P), and binder polyvinylidene fluoride (PVDF) are mixed in a certain mass ratio; then N-methylpyrrolidone (NMP) is added as a solvent to prepare a positive electrode slurry with a solid content of 60wt%, and stirred evenly, and then the positive electrode slurry is evenly coated on one surface of a positive electrode current collector (aluminum foil) with a thickness of 15μm, and then dried, cold pressed, slit, and cut to form a positive electrode material layer 220, and the positive electrode sheets 200 of Examples 1 to 11 and Comparative Example 1 are obtained. The single-sided thickness of the positive electrode material layer 220 is 100μm.
[0117] Among them, in the positive electrode material layer 220 of the positive electrode sheet 200 of Examples 1 to 11 and Comparative Example 1, the value of the mass fraction A3 of the composite particles 100 is as shown in Table 1.
[0118] 2. Preparation of negative electrode sheet 320:
[0119] The negative electrode active material artificial graphite, thickener sodium carboxymethyl cellulose (CMC), conductive carbon black (Super-P) and binder styrene butadiene rubber latex (SBR) are mixed in a mass ratio of 96:2:1:1, deionized water is added, and a negative electrode slurry with a solid content of 50wt% is prepared and stirred evenly. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector (copper foil) with a thickness of 6μm, and a negative electrode material layer is formed after drying, cold pressing, stripping, and cutting to obtain a negative electrode sheet 320. The single-sided thickness of the negative electrode active material layer is 70μm.
[0120] 3. Preparation of electrolyte 330:
[0121] In an argon atmosphere glove box with a moisture content of ≤1ppm, ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 1:1:1, and an ether solvent and a film-forming additive are added and mixed again, and then the dried solute is dissolved in the solvent, and stirred until the solute is completely dissolved and uniformly obtained to obtain an electrolyte 330. The solute in the electrolyte 330 is lithium hexafluorophosphate, and the molar concentration of the lithium hexafluorophosphate is 1.2 mol / L.
[0122] 4. Preparation of diaphragm 310:
[0123] The separator 310 is a 16 um polyethylene film (PE).
[0124] 5. Assembly of battery 300:
[0125] The positive electrode sheet 200, the separator 310, and the negative electrode sheet 320 are stacked in order so that the separator 310 is located between the positive electrode sheet 200 and the negative electrode sheet 320 to play an isolating role, and then they are wound into a bare battery cell; after welding the pole ears, the bare battery 300 is placed in an outer packaging shell, and after drying, the above-mentioned electrolyte 330 is injected, and after vacuum packaging, standing, forming, shaping, etc., the implementation batteries 1 to 11 and the comparison battery 1 are finally prepared.
[0126] Among them, the positive electrode sheet 200 of Example 1 is assembled in the implementation battery 1, the positive electrode sheet 200 of Example 2 is assembled in the implementation battery 2, the positive electrode sheet 200 of Comparative Example 1 is assembled in Comparative Battery 1, and so on.
[0127] Table 1 below shows the composition parameters of the composite particles 100 and the positive electrode sheet 200 of Examples 1 to 11 and Comparative Example 1.
[0128] Table 1: Composition parameters of the composite particles 100 and the positive electrode sheet 200 of Examples 1 to 11 and Comparative Example 1.
[0129]
[0130]
[0131] It can be seen from Table 1 that the composite particle 100 of Comparative Example 1 does not include the second coating layer 130 .
[0132] Performance test of battery 300:
[0133] 1. Initial capacity test of battery 300:
[0134] The following treatments were performed on implementation batteries 1 to 11 and comparison battery 1: in the formation stage of battery 300: battery 300 was charged at 0.02C for 10 hours at 45°C; degassed and allowed to stand for 24 hours; in the capacity separation stage of battery 300: at 25°C, charged to 3.65V at 0.5C, then charged to 0.05C at a constant voltage, left for 10 minutes, and discharged to 2.5V at 0.5C, and the resulting capacity was the initial capacity.
[0135] The initial capacity values of implementation batteries 1 to 11 and comparison battery 1 are shown in Table 2.
[0136] 2. Battery 300 cycle performance test:
[0137] (1) Cyclic climbing height test of battery 1 to battery 11 and comparison battery 1:
[0138] The implementation batteries 1 to 11 and the comparative battery 1 were placed in a constant temperature box and the temperature was set at 25°C. The implementation batteries 1 to 11 and the comparative battery 1 were treated as follows: ① Charge the battery 300 to 3.65V at 0.5P; ② Leave it for 10 minutes; ③ Discharge the battery 300 to 2.5V at 0.5P; ④ Leave it for 10 minutes; ⑤ Repeat the above steps for 500 cycles.
[0139] In the above 500 cycles, the capacity discharged in each cycle is divided by the capacity discharged in the first cycle to obtain the capacity retention rate. The maximum value of the capacity retention rate within 500 cycles minus 100% will give the value of the climbing height.
[0140] It can be understood that the higher the climbing height, the more obvious the capacity climbing phenomenon of the battery 300 is, and the worse the cycle performance of the battery 300 is.
[0141] (2) Capacity retention test of implementation battery 1 to implementation battery 11 and comparison battery 1 after 500 cycles at 25° C.:
[0142] The above-mentioned implementation batteries 1 to implementation batteries 11 and comparative battery 1 were subjected to constant power charge and discharge cycle tests on a charge and discharge instrument, the test temperature was 25°C, the charge and discharge rate was 0.5C (the size of the charge and discharge current is usually expressed by the charge and discharge rate, and the calculation formula of the charge and discharge current is: charge and discharge current = charge and discharge rate × rated capacity of battery 300), and the charge and discharge voltage window was 2.5V~3.65V (that is, the charging cut-off voltage of battery 300 is 3.65V, and the discharging cut-off voltage of battery 300 is 2.5V); the capacity retention rates of implementation batteries 1 to implementation batteries 11 and comparative battery 1 after 500 cycles were calculated, and the values of the capacity retention rates of implementation batteries 1 to implementation batteries 8 and comparative battery 1 after 500 cycles at 25°C are shown in Table 2.
[0143] The calculation formula is: capacity retention rate after the nth cycle = (discharge capacity after the nth cycle / discharge capacity of the first cycle) × 100%.
[0144] A complete charge and discharge is usually called a charge and discharge cycle, that is, the battery 300 is first charged from 2.5V to 3.65V, and then discharged from 3.65V to 2.5V, thus forming a charge and discharge cycle. Cycle N times means repeating the above process N times.
[0145] Table 2 shows the capacity retention rates of the implementation batteries 1 to 11 and the comparative battery 1 after 500 cycles.
[0146] Table 2 below shows the performance parameters of implementation batteries 1 to 11 and comparison battery 1.
[0147] Table 2: Performance parameters of implementation batteries 1 to 11 and comparative battery 1.
[0148]
[0149] Please refer to Table 1 and Table 2. From the data of Example 2 and Comparative Example 1, it can be seen that the composite particle 100 of Example 2 includes a core 110, a first coating layer 120 and a second coating layer 130, while the composite particle 100 of Comparative Example 1 only includes the core 110 and the first coating layer 120, and does not include the second coating layer 130, so that the initial capacity of the implementation battery 2 is higher than the initial capacity of the comparative battery 1, the cycle climbing height of the implementation battery 2 is lower than the cycle climbing height of the comparative battery 1, and the capacity retention rate of the implementation battery 2 after 500 cycles is higher than that of the comparative battery 1 after 500 cycles. This is because: the composite particles 100 of Example 2 include a second coating layer 130, and the ionic conductivity of the second coating layer 130 is variable. The ionic conductivity of the second coating layer 130 can be adjusted to control whether lithium ions can pass through the second coating layer 130, so that the lithium ions escaped from the inner core 110 do not participate in the charge and discharge cycle of the battery 300, slowing down the capacity climbing problem, and ultimately making the implementation battery 2 have a lower cycle capacity climbing height, a higher initial capacity and a higher cycle capacity retention rate than the comparison battery 1.
[0150] It can be seen from the data of Examples 1 to 3 that, under the same other conditions, in the positive electrode material layer 220 of Examples 1 to 3, the mass fraction A3 of the composite particles 100 satisfies 5%≤A3≤15%, and as the mass fraction of the composite particles 100 increases, the initial capacity of the corresponding battery 300 shows a decreasing trend, the cycle climbing height gradually decreases, and the cycle capacity retention rate shows an increasing trend. This shows that: in Example 1, when the mass fraction A3 of the composite particles 100 is relatively small, the compaction density of the positive electrode plate 200 is relatively small, and the content of lithium ions released by the composite particles 100 is relatively small, and it is difficult to replenish the lithium ions consumed in the electrolyte 330. Although the positive electrode plate 200 has a higher initial capacity, the cycle performance of the battery 300 is poor. Therefore, the cycle climbing height in the implementation battery 1 is relatively large, and the cycle capacity retention rate is relatively small. In Example 3, when the mass fraction A3 of the composite particles 100 is too large, the composite particles 100 account for too much in the positive electrode material layer 220, and the mass fraction of the active particles 221 is too small. The lithium ions in the composite particles 100 will not return to the composite particles 100 after being released, that is, the composite particles 100, as an irreversible lithium supplement material, do not participate in the charge and discharge cycle of the battery 300, so that the initial capacity of the implementation battery 3 is low, but the mass fraction of the composite particles 100 is still within a reasonable range, so that the composite particles 100 can be used as an irreversible lithium supplement material, so that the implementation battery 3 has a smaller cycle climbing height and a higher cycle capacity retention rate. In Example 2, the mass fraction of the composite particles 100 is within a relatively reasonable range, and the composite particles 100 and the active particles 221 cooperate with each other to fully utilize the space of the positive electrode material layer 220, so that the positive electrode plate 200 has a higher compaction density; on the other hand, the core 110 of the composite particle 100 can release lithium ions to timely replenish the lithium ions consumed in the electrolyte 330. The composite particle 100 can be used as an irreversible lithium supplement material, which can improve the initial capacity of the positive electrode plate 200 while slowing down the capacity climb of the battery 300, so that the battery 300 has both a higher initial capacity and a higher energy density, and the battery 300 has better cycle performance.
[0151] It can be seen from the data of Example 2, Example 4 and Example 5 that, under the same other conditions, in the composite particles 100 of Example 2, Example 4 and Example 5, the median particle size D1 of the composite particles 100 all satisfies 1μm≤D1≤10μm, and as the median particle size of the composite particles 100 increases, the initial capacity of the corresponding battery 300 shows a decreasing trend, the cycle climbing height shows a decreasing trend, and the cycle capacity retention rate shows a decreasing trend, which shows that: in Example 4, the median particle size of the composite particles 100 is relatively small, and the degree of improvement in the cycle performance of the battery 300 is relatively small, so that the cycle climbing height of the implementation battery 4 is relatively high. In Example 5, the median particle size of the composite particles 100 is relatively large, but the median particle size of the composite particles 100 is still within a reasonable range, and the lithium ions released by the core 110 can escape from the composite particles 100 and irreversibly replenish lithium to slow down the occurrence of the capacity climbing phenomenon, so that the cycle climbing height of the implementation battery 5 is relatively small. In Example 2, the median particle size of the composite particle 100 is neither too large nor too small. The composite particle 100 includes a core 110, a first coating layer 120 and a second coating layer 130. The first coating layer 120 can improve the conductivity of the large-sized composite particle 100. The second coating layer 130 can control the ionic conductivity to control the lithium ions to pass through the second coating layer 130 from the core 110, but cannot return to the inside of the composite particle 100, so that the lithium iron phosphate of the core 110 can replenish the lithium ions consumed by the electrolyte 330 and the lithium ions released by the core 110 do not participate in the charge and discharge cycle, thereby slowing down the capacity climbing problem caused by the large-sized composite particle 100 when applied to the positive electrode plate 200, and the composite particle 100 has good performance. Therefore, the median particle size of the composite particle 100 can be adjusted to make the battery 300 have a lower climbing height and a higher cycle retention rate.
[0152] It can be seen from the data of Example 2, Example 6 and Example 7 that, under the same other conditions, in the composite particles 100 of Example 2, Example 6 and Example 7, the mass fraction A1 of the first coating layer 120 satisfies the range of 0.5%≤A1≤4%, and as the mass fraction of the first coating layer 120 increases, the initial capacity of the corresponding battery 300 first increases and then decreases, the cycle climbing height tends to remain unchanged, and the cycle capacity retention rate shows a trend of first increasing and then decreasing. This shows that: in Example 6, the mass fraction of the first coating layer 120 is relatively small, and the first coating layer 120 is difficult to fully improve the conductivity of the composite particle 100, which increases the difficulty and impedance of the lithium ions released from the lithium iron phosphate in the core 110 to pass through the first coating layer 120, affecting the lithium ion transmission performance, thereby causing the cycle performance of the battery 300 to deviate, and the cycle capacity retention rate of the implemented battery 6 is relatively low. In Example 7, the mass fraction of the first coating layer 120 is too large, which increases the difficulty and impedance of the lithium ions released from the lithium iron phosphate in the core 110 to pass through the first coating layer 120, so that the composite particle 100 is difficult to play the lithium supplement performance, and finally reduces the initial capacity of the positive electrode plate 200, so that the initial capacity of the implementation battery 7 is low. In Example 2, the mass fraction of the first coating layer 120 is neither too large nor too small, the first coating layer 120 can not only improve the conductivity of the composite particle 100, but also the first coating layer 120 can be evenly coated on the periphery of the core 110 to prevent the lithium ions of the lithium iron phosphate in the core 110 from being released, and can prevent the first coating layer 120 from cracking and causing the iron in the lithium iron phosphate to dissolve, so that the composite particle 100 can play the lithium supplement performance and have a longer service life, so as to improve the initial capacity of the positive electrode plate 200, so that the implementation battery 2 has a higher initial capacity and better cycle performance.
[0153] It can be seen from the data of Example 2, Example 8 and Example 9 that, under the same other conditions, in the composite particles 100 of Example 2, Example 8 and Example 9, the mass fraction A2 of the second coating layer 130 satisfies the range of 0.5%≤A2≤3%, and as the mass fraction of the second coating layer 130 increases, the initial capacity of the corresponding battery 300 shows a decreasing trend, the cycle climbing height shows a decreasing trend, and the cycle capacity keeps increasing first and then decreasing, which shows that: in Example 8, the mass fraction of the second coating layer 130 is too small, and the second coating layer 130 is difficult to completely and evenly cover the composite particles 100. The first coating layer 120 is coated on the periphery, and the second coating layer 130 has insufficient passivation ability for large currents. When the battery 300 is in the discharge process, the composite particle 100 is in a large current environment and loaded with a second current. The ionic conductivity of the second coating layer 130 is relatively high, which may also cause the lithium ions released from the composite particle 100 to still pass through the second coating layer 130 and the first coating layer 120 and enter the core 110. In other words, the lithium ions released from the composite particle 100 participate in the charge and discharge cycle of the battery 300, and the composite particle 100 cannot be used as an irreversible lithium supplement material. In the process of the lithium ions released from the composite particles 100 returning to the core 110 from the negative electrode sheet 320, on the one hand, the capacity of the battery 300 may be increased, thereby reducing the cycle stability of the battery 300; on the other hand, the path of the ions returning from the negative electrode sheet 320 to the core 110 is too long, which will increase the impedance of the battery 300, thereby reducing the cycle performance of the battery 300, so that the cycle climbing height of the implementation battery 8 is too large and the cycle capacity retention rate is low. In Example 9, the mass fraction of the second coating layer 130 is too large. When the composite particles 100 are applied to the battery 300 and the battery 300 is in a charging state, even if the composite particles 100 are loaded with a first current, the lithium ions released from the lithium iron phosphate in the core 110 are difficult to pass through the second coating layer 130, and the composite particles 100 are difficult to release lithium ions, so that the composite particles 100 cannot provide lithium ions for the battery 300, reducing the initial capacity of the positive electrode sheet 200, so the initial capacity of the implementation battery 9 is low.In Example 2, the mass fraction of the second coating layer 130 is neither too large nor too small. When the composite particle 100 is in a small current environment and loaded with a first current, the second coating layer 130 has a larger first ion conductivity, and the lithium iron phosphate of the inner core 110 can separate lithium ions and allow the lithium ions to escape. When the composite particle 100 is in a large current environment and loaded with a second current, the second coating layer 130 has a smaller second ion conductivity, and the lithium ions escaped from the lithium iron phosphate of the composite particle 100 cannot return to the composite particle 100, so that the lithium iron phosphate in the composite particle 100 can be used as an irreversible lithium supplement material to slow down the capacity climbing problem caused by the large-sized positive electrode active material applied to the battery 300, and ultimately enable the implemented battery 2 to have a higher initial capacity, a lower cycle climbing height and a higher cycle capacity retention rate.
[0154] From the data of Example 2, Example 10 and Example 11, it can be seen that under the same other conditions, the median particle size D1 of the composite particles 100 of Example 2, Example 10 and Example 11 all meet the range of 1μm≤D1≤10μm, and D1 / D2 all meet the range of 2≤D1 / D2≤15. In Example 10, the median particle size D1 of the composite particles 100 is 1μm, and the value of D1 / D2 is 2. In other words, the particle size of the active particles 221 is relatively large, and is at least 0.5μm, so that the initial capacity of the implemented battery 10 is relatively low, the cycle climbing height is relatively large, and the capacity retention rate of 500 cycles is relatively high. In Example 10, when the median particle size of the composite particles 100 is relatively small, the capacity of the composite particles 100 for lithium supplementation will be higher, which can alleviate the problem of low gram capacity of the active particles 221 to a certain extent, but the improvement is small, so that the initial capacity of the implemented battery 10 is relatively low. Furthermore, the particle size of the active particles 221 is relatively large, and the larger-sized active particles 221 have poor dynamic performance during the cycle process. The active particles 221 are easily attenuated and cracked, which makes the cycle performance of the implementation battery 10 poor, the cycle climbing height of the implementation battery 10 is relatively large, and the capacity retention rate of 500 cycles is relatively high. In Example 11, the median particle size D1 of the composite particles 100 is 3μm, and the value of D1 / D2 is 15. In other words, the particle size of the active particles 221 is relatively small and is 0.2μm, so that the initial capacity of the implementation battery 11 is relatively high, the cycle climbing height is relatively small, and the cycle capacity retention rate is relatively high. This shows that when the particle size of the active particles 221 is small, it should match the composite particles 100 with a larger median particle size, and make D1 / D2 within a reasonable range, which is beneficial to improving the compaction density of the positive electrode plate 200 on the one hand, and on the other hand, the composite particles 100 cooperate with the active particles 221, which is beneficial to the composite particles 100 to play the lithium supplement function, and can avoid the problem of capacity climbing, reduce the cycle climbing height, and improve the cycle performance of the implementation battery 11. In addition, in the data of Example 2, Example 10 and Example 11, the initial capacity of the implementation battery 2 is higher than the initial capacity of the implementation battery 10, and the cycle performance of the implementation battery 2 is better than the cycle performance of the implementation battery 10 and the implementation battery 11, which shows that when D1 / D2 is in the preferred range of 5≤D1 / D2≤10, the corresponding battery 300 has a higher initial capacity and better cycle performance, which shows that by adjusting the value of D1 / D2, the cycle performance of the battery 300 can be adjusted.
[0155] See also Figure 4 and Figure 5 The present application provides an electrical device 400 , which includes: a device body 410 and a battery 300 provided in the present application, and the battery 300 supplies power to the device body 410 .
[0156] It can be understood that the battery 300 is electrically connected to the device body 410 .
[0157] In this embodiment, the positive electrode sheet 200 of the battery 300 includes the composite particles 100 provided in this application. The composite particles 100 are large-sized positive electrode active materials, which cooperate with the active particles 221 to make the positive electrode sheet 200 have a large compaction density. At the same time, the composite particles 100 can be used as an irreversible lithium supplement material to release lithium ions and replenish the lithium ions lost in the electrolyte 330 when the first current is loaded, so that the positive electrode sheet 200 has a higher initial capacity. Furthermore, the composite particles 100 are provided with a second coating layer 130 with variable ion conductivity to prevent the lithium ions released from the core 110 from returning to the core 110, slowing down the capacity climbing phenomenon, and avoiding the increase of the impedance of the battery 300 due to the long path of lithium ions returning from the negative electrode sheet 320 to the composite particles 100. The battery 300 provided in this embodiment has both high energy density and initial capacity, and has good cycle performance. Furthermore, the battery 300 can provide stable power to the device body 410, which is beneficial to improving the user experience.
[0158] Optionally, the power-consuming device 400 of the embodiment of the present application may be, but is not limited to, a portable electronic device such as a mobile phone, a tablet computer, a laptop computer, a desktop computer, a smart bracelet, a smart watch, an e-reader, a game console, etc. It may also be a vehicle such as a car, a truck, a car, a truck, a truck, a motor vehicle, a high-speed train, an electric vehicle, etc. In addition, it may also be various household appliances, etc. The present application Figure 4 The electrical equipment 400 of the embodiment is an energy storage battery cabinet.
[0159] It can be understood that the electric device 400 described in this embodiment is only a form of the electric device 400 used by the battery 300, and should not be understood as a limitation on the electric device 400 provided in this application, nor should it be understood as a limitation on the electric device 400 provided in each embodiment of this application.
[0160] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, provided that there is no contradiction between them.
[0161] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.
Claims
1. A composite particle, characterized in that: The composite particles include: a core, the core comprising lithium iron phosphate; A first coating layer, the first coating layer coating the outer periphery of the inner core, the first coating layer being a carbon layer; and The second coating layer is coated on the outer periphery of the first coating layer, the second coating layer is a metal oxide layer, and the ion conductivity of the second coating layer is variable.
2. The composite particles according to claim 1, characterized in that When the composite particles are loaded with a first current, the second coating layer has a first ionic conductivity; when the composite particles are loaded with a second current, the second coating layer has a second ionic conductivity, wherein the first current is smaller than the second current, and the first ionic conductivity is greater than the second ionic conductivity.
3. The composite particles according to claim 1, characterized in that As the current loaded on the composite particles gradually increases, the ionic conductivity of the second coating layer gradually decreases.
4. The composite particles according to claim 1, characterized in that The second coating layer is selected from at least one of Al2O3, MgO, TiO2, SiO2, ZnO, SnO2 and ZrO2.
5. The composite particles according to claim 1, characterized in that The range of the median particle size D1 of the composite particles is: 1 μm≤D1≤10 μm.
6. The composite particles according to claim 1, characterized in that In the composite particles, the mass fraction A1 of the first coating layer is in the range of 0.5%≤A1≤4%.
7. The composite particles according to claim 4, characterized in that In the composite particles, the mass fraction A2 of the second coating layer is in the range of 0.5%≤A2≤3%.
8. A positive electrode sheet, characterized in that: The positive electrode sheet comprises: a positive electrode current collector layer; and A positive electrode material layer, the positive electrode material layer is arranged on at least one surface of the positive electrode current collector layer, the positive electrode material layer comprises active particles and composite particles according to any one of claims 1 to 7, and the median particle size of the composite particles is larger than the median particle size of the active particles.
9. The positive electrode sheet according to claim 8, characterized in that: The median particle size of the composite particles is D1, and the median particle size of the active particles is D2, and the relationship is satisfied: 2≤D1 / D2≤15.
10. The positive electrode sheet according to claim 8, characterized in that: In the positive electrode material layer, the mass fraction A3 of the composite particles is in the range of 5%≤A3≤15%.
11. A battery, characterized in that: The battery comprises: The positive electrode sheet according to any one of claims 8 to 10; A diaphragm, the diaphragm being arranged on one side of the positive electrode plate; A negative electrode plate, the negative electrode plate being disposed on a side of the diaphragm away from the positive electrode plate; and An electrolyte is used to soak at least a portion of the positive electrode sheet, the separator and the negative electrode sheet.
12. An electrical device, characterized in that: The electrical equipment includes: The device itself; and The battery of claim 11, wherein the battery is used to power the device body.